HUBUNGAN TINGKAT KECEMASAN IBU DENGAN TERJADINYA PERSALINAN LAMA (PROLONG) PADA IBU BERSALIN KALA 1 FASE AKTIF PRIMIGRAVIDA DI RUMAH SAKIT AURA SYIFA KABUPATEN KEDIRI TAHUN 2019 - Ira Titisari; Citra DewiFitri Setiani; Sumy Dwi Antono (coba, 2020)
Introduction: Labor is a process of opening and thinning the cervix and the fetus descends into the birth canal. The aim of this study was to determine the relationship of level of anxiety with the occurrence of prolonged labor (prolongation) at the time of delivery of Primigravida active phase 1 in Aura Syifa Hospital, Kediri. Method: The design of this study was cross-sectional research. An accidental sampling technique with a sample of 33 respondents was taken for this research. The research instrument used questionnaires and partographs. Data analysis using the Coefficient Contigensi test with a significant level of 0.05. Result: The results showed a significant relationship between the Anxiety Level and the occurrence of prolonged labor in the primigravida phase 1 in the Aura Syifa Hospital, Kediri. The closeness of the relationship between the two variables was medium, and the direction of the relationship between the two variables was positive. Discussion: Based on the results of these studies, health workers should teach relaxation techniques such as hypnobirthing during pregnancy to reduce anxiety during labor so it will not cause prolonged labor.